ISM-CODE AS A LEGAL PROTECTION OF USE SHIPS ARE NOT CONFORT WITH MARINE STANDARD IN INDONESIA - Anirut Chuasanga; Ong Argo Victoria (Jurnal Pembaharuan Hukum, 2021)
Transportation in general in Indonesia is facing many challenges, but all possibilities that will occur can be anticipated by structuring a more resilient national transportation system. This study aims to determine and understand the application of the ISM-Code to be used as legal protection from the use of ships that are not of marine standards. The research method used is the normative research method, which is a legal writing method that aims to obtain library legal materials by collecting and analyzing legal materials related to the problem. The results of this study are, first. In the application of the ISM-Code it is used as a legal protection from the use of ships that are not standard marine standards. There are still many shipping companies that issue policies that are not standard ISM-Code or do not meet the elements of Article 9 of the Minister of Transportation Number 45 of 2012 concerning Ship Safety Management Systems. And secondly the ISM-Code Required as Legal protection from the use of ships that do not meet maritime standards is the form of legal protection contained in the ISM-Code.